2010
DOI: 10.1179/030192310x12700328925903
|View full text |Cite
|
Sign up to set email alerts
|

Composition change in oxide inclusions of stainless steel by heat treatment

Abstract: It is known that the oxide composition in stainless steel changes during heat treatment; however, the precise conditions to cause change are not clear. Therefore, the conditions necessary to change the oxide composition by heat treatment have been investigated using steels with different concentrations of Si, Mn, Ni and Cr. The MnO-SiO 2 type inclusions changed into MnO-Cr 2 O 3 type inclusions in steel containing 18%Cr and 8%Ni after heat treatment with a low silicon concentration. At high silicon content, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 8 publications
2
37
0
1
Order By: Relevance
“…Shibata et al [1,2] investigated the solid-state reaction at the interface between Fe-Cr steel and MnO-SiO 2 oxide created by heat treatment at 1473 K (1200°C) using the diffusion couple method. It was shown that MnO-SiO 2 -type inclusions changed to MnO-Cr 2 O 3 -type inclusions in the case of low Si content in the steel.…”
Section: Introductionmentioning
confidence: 99%
“…Shibata et al [1,2] investigated the solid-state reaction at the interface between Fe-Cr steel and MnO-SiO 2 oxide created by heat treatment at 1473 K (1200°C) using the diffusion couple method. It was shown that MnO-SiO 2 -type inclusions changed to MnO-Cr 2 O 3 -type inclusions in the case of low Si content in the steel.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Kimura et al 6) reported the change in the chemical composition of the oxide inclusions of stainless steel without the hot rolling process. Shibata et al 7) also recently investigated the effect of Cr content in the Fe-Cr alloy deoxidized by Mn and Si on the change in the chemical composition of the © 2011 ISIJ oxide inclusions without the hot rolling process by heat treatment at 1 473 K for 60 min. The change in the chemical composition of the oxide inclusions from MnO-SiO2 to MnO-Cr2O3 has been observed above 1 mass% Cr with low Si concentrations by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 And while the sulphur improves the machining, it also causes a decrease in the corrosion resistance 4 and a slight lowering of the toughness and a general decrease of the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%